The Objectives (Maqasid Shari'ah) of Observing Modesty and Women's Modest Dress In The Holy Quran - Sadatmoosavi, Zohreh; Wan Ali, Wan Zailan Kamaruddin; Shokouh, Mohammad Ali (Online Journal of Research in Islamic Studies, 2015)
In all of divine religions, God has established His law for the aims of the people's welfare and happiness in this world and hereafter life. In Islamic teachings, Maqasid al-Shari'ah comprises those benefits, welfare and advantages which Allah has revealed in His law. One of the regulations which Quran has established for keeping the human communication from the damages is regarding the observation of modesty and modest dress. Nowadays, along with the development of some phenomena such as humanism, secularism, modernism and feminism, consideration to divine providence and law have been weakened. Therefore, the consideration to real benefits of human and effects of spiritual and hereafter of human actions are lowered. Also, political and economic motivations have questioned many cultural traditions. The objective of this study is to explore the Maqasid al-Shari'ah of modesty (for men and women) and women wearing the kinds of modest dress in Quran (Jilbab and Khimar) as a symbol of religious devotion.